Avaliação de híbridos e fungicidas para controle de alternaria spp. em canola - Scheffer, Alexandre Spalding (2017)
The Alternaria spp. is one of the main fungal diseases of canola, being responsible for damages and losses in the culture. Taking into account the importance of the disease, the goals of this job were following: a) to verify if there is variability of resistence between canola hybrids as to the . Alternaria spp. infection; b) to verify if the Alternaria spp. affects the physiological quality of canola seeds and what active ingredients are efficient in its control; and c) to test if fungicide treatments applied in a preventive and eradication way are efficient to control the fungus artificially inoculated in canola plants. Thechniques of fungus inoculation in seeds and in the aerial part of plants make it possible to obtain hygly infected seeds and plants with the inoculum for later study. The method used to inoculate the fungus in seeds consisted in the contact of the seed with the inoculum on culture medium containing mannitol water restrictor. In order to inoculate the fungus in the aerial part it was used a spraying suspension of conidia and the plants were incubated with controlled conditions to the establishment of the disease. The experiments were conducted in laboratories, in inoculation chambers and in a greenhouse. In order to evaluate if there is variability of canola hybrids in fungus resistance, the experimental desing used was completely randomized with six repetitions, evaluating the number of Alternaria spp. lesions per plant, the incidence of leaves with lesions per plant and the average lesion size. As to evaluate if the fungus affects the canola physiological quality of canola seeds and what active ingredients are efficient to its control, the experimental desing used was completely randomized with eight repetitions in laboratories and in random blocks with four repetitions in the greenhouse experiment, evaluating the number of colonies of Alternaria spp., percentage of fungus control, germination, vigor, seed germination speed index, hypocotyl height, primary root length, seedling emergence at seven and twelve days after the sowing, shoot height and root lenght. In order to evaluted if fungicides applied in a preventive and eradication way are efficient to control the fungus in canola plants, the experimental desing used was completely randomized with six repetitions, evaluating the incidence of silica infected with Alternaria spp. per plant, number of lesions per silica, average lesion size and percentage control of the fungicides. There is variability in canola hybrids as to the resistance to Alternariaspp. The hybrids HYOLA 61 and HYOLA 76 present higher resistance to the inoculated fungus in canola plants in relation to the other hybrids, and they do not present a significant difference in relation to the hybrids ALHT M6, Diamond and HYOLA 433, to the incidence of leaves with lesions and the hybrid HYOLA 571CL to average lesion size of Alternaria spp. The colonization of Alternaria spp. in canola seeds was efficient. The control without Alternaria spp. and without fungicide present a higher percentage of germination of seeds, compared to the control inoculated with Alternaria spp. and without fungicide. The active ingredients diphenoconazole, iprodione and metalaxyl-M + fludioxonil present control of Alternaria spp. inoculated in canola seeds. Being that in 2015 the active ingredients carbendazim + thiram + metalaxyl-M + fludioxonil, metalaxyl-M + thiabendazole + fludioxonil and pyraclostrobin + thiophanate-methyl + fipronil, and in 2016 carbendazim + thiram, thiophanate-methyl + fluazinam and thiophanate-methyl + metalaxyl-M + fludioxonil, also presented control of the fungus. The active ingredient iprodione stands out in the control of the inoculated fungus in canola seeds, and in 2016 differed from the inoculated control with the fungus and without fungicide, for the germination variables, seed germination speed index, primary root length and .Evaluation of hybrids and fungicides to control Alternaria spp. in canola shoot height. The fungicide applications with azoxystrobin + cyproconazole, iprodione and flutriafol are efficient to control Alternaria spp. inoculated in canola plants, both in preventive and in eradication application. In preventive application, the tested fungicides differ from the control inoculated with the fungus in relation to the average lesion size.